PI/PISMC control of hydraulically actuated active suspension system - Md. Sam, Yahaya; Hudha, Khisbullah (2006)
The purpose of this paper is to present a robust strategy in controlling a hydraulically actuated active suspension system. The controller consists of the two controller loops namely inner loop controller for force tracking control of the hydraulic actuator and outer loop controller to reject the effects of road induced disturbances. The outer loop controller utilized a proportional integral sliding mode control (PISMC) scheme. Whereas, proportional integral (PI) control is used in the inner loop controller to track the hydraulic actuator in such a way that it able to provide the actual force as close as possible with the optimum target force produced by the PISMC controller. A quarter-car model is used in this study and the performance of the controller is compared with the state feedback controller and the existing passive suspension system. A simulation study is performed to prove the effectiveness and robustness of the control approach. Force tracking performance of the hydraulic actuator is also investigated.